Modeling and non Linear Dynamic Analysis of the Chaotic Colpitts Oscillator up to 1 GHz - C. Rouifed; A. Ouslimani; M. Laghrouche (Algerian Journal of Research and Technology (AJRT), 2020)
In this paper, we consider a Colpitts oscillatos as a model for nonlinear dynamic analysis. In particular, we perform a bifurcation analysis using a real and theorical model of the Colpitts oscillator. This analysis, simulated with Matlab, shows a difference between the two models while calculating their parameters. Moreover, in order to fixe the optimal values of the circuit’s component, spectrum simulation under ADS have been performed up to 1GHz. It shows a chaos bandwidth of 600 MHz.